The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1088/1361-6501/ad1eb3
|View full text |Cite
|
Sign up to set email alerts
|

Fault diagnosis of rotating machinery using novel self-attention mechanism TCN with soft thresholding method

Li Ding,
Qing Li

Abstract: Rotating machinery (e.g., rolling bearing and gearbox) are usually operated in high-risk and vulnerable environments such as time-varying loads and poor lubrication. Timely assessment of the operational status for rotating machinery is crucial to prevent damage caused by potential failure and shutdown, which significantly enhances the reliability of mechanical systems, prolongs the service life of critical components in rotating machinery, and minimizes unnecessary maintenance costs. To this regard, in this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Unfortunately, noise interference is often ignored in these approaches. Many studies on noise-robust fault diagnosis have shown that using thresholding operations as a network layer for feature extraction from convolutional layers is a viable solution [27]. However, each soft and hard thresholding has limitations, so it is necessary to balance them without adding too much model complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, noise interference is often ignored in these approaches. Many studies on noise-robust fault diagnosis have shown that using thresholding operations as a network layer for feature extraction from convolutional layers is a viable solution [27]. However, each soft and hard thresholding has limitations, so it is necessary to balance them without adding too much model complexity.…”
Section: Introductionmentioning
confidence: 99%